Malma station : a novel - Schulman, Alex, 1976- (Pegasus Crime, 2025)
"A train races through a stark summer landscape. Everyone on board is traveling to Malma Station, and no one realizes how their fates are intertwined. On board the train to Malma Station are a married couple in crisis, a single dad and his young daughter, and a woman searching for the answer to a mystery her mother left behind. The enigmatic Harriet, the controlling Oskar, and the searching Yana - each of these characters carries within them the scars of what has come before. Malma Station traces the crooked lines of family and history and shows how memories morph to take new shape, postulating that perhaps the past is actually what we can change, rather than the future. The narrative builds like a train hurtling through time, each chapter a separate car hooking into the next. Malma Station is at once an enchanting and gut-wrenching novel about family secrets and injustices passed on through generations - and a suspenseful hunt for a truth with the power to change everything." --